Effects of preference and sensory modality on behavioural reaction in patients with disorders of consciousness. (24th August 2017) - Heine, L.; Tillmann, B.; Hauet, M.; Juliat, A.; Dubois, A.; Laureys, S.; Kandel, M.; Plailly, J.; Luauté, J.; Perrin, F
ABSTRACT: Background : Reliable evaluation of patients with unresponsive wakefulness syndrome (UWS) or in a minimally conscious state (MCS) remains a major challenge. It has been suggested that the expression of residual cerebral function could be improved by allowing patients to listen to their favourite music. However, the potential effect of music on behavioural responsiveness, as well as the effect of preferred stimuli in other sensory modalities (e.g. olfaction), remain poorly understood. Objective : The aim of our study was to investigate the effect of sensory modality (auditory versus olfactory) and preference (preferred versus neutral) of the test stimuli on patients' subsequent performance on the Coma Recovery Scale-Revised (CRS-R). Research design : Within-subject design because of inter-individual differences between patients. Methods and procedures : We studied four items from the CRS-R (visual pursuit using a mirror, auditory localization of the own name and two movements to command) in 13 patients (7 MCS; 6 UWS). Main outcomes and results : Auditory stimuli triggered higher responsiveness compared to olfactory stimuli, and preferred stimuli were followed by higher scores than did neutral stimuli. Conclusions : Findings suggest that preferred auditory stimuli at the bedside contribute to the expression of residual function and could improve the diagnostic assessment.